Teachers ' Inclusive Classroom Practices: The Role of Self-efficacy and Demographic Variables - Omoro, Martanus Ochola; Possi, Mwajabu A.K. (Papers in Education and Development, 2023)
The purpose of this quantitative, correlational study was to examine the role of teachers ' self-efficacy and demographic variables during their inclusive practices. A structured questionnaire was used in data collection. The sample of the study consisted of 254 in-service teachers from 18 inclusive primary schools in Tanzania. The study found a statistically significant and positive relationship between teacher self-efficacy and their inclusive practices. Regression analysis indicated that teachers ' self-efficacy, particularly in instructional practices, as well as teacher demographics (except gender, age, and education) were considered to be significant factors that predict their inclusive practices. Thus, the study recommends for educational interventions to promote teachers ' competence, self-confidence, knowledge, and skills in order to promote inclusive practices in schools in Tanzania. Keywords: Teacher self-efficacy, inclusion, inclusive education, student with disabilities, and inclusive classroom practices